Analisis Potensi Pengembangan Objek Wisata Alam Kabupaten Kolaka Provinsi Sulawesi Tenggara - Wibowo, Andhika Sutrisno; , Dr. Kuswaji Dwi Priyono, M.Si (2017)
Kolaka Regency is a region in Southeast Sulawesi Province. Many potentials of natural tourism owned by this region with the unique enchantment and admirable variety which are seldom to be found in other places. So far, the development of the natural tourism in this area has not been managed optimally because there are several obstacles which obstruct the development of each natural tourism obj ects. Related to the above mentioned, the problem statements of this research are: (1) How is the potential level of the natural tourism objects in Kolaka regency? (2) What are dominant factors that support and obstruct the development of the natural tourism objects?(3) How is the development strategy of the natural tourism objects in Kolaka Regency?. The purposes of the research that want to be reached are: (1) To classify the potential level of the natural tourism objects in Kolaka regency. (2) To know the dominant factors that support and obstruct the development of the natural tourism object, and (3) To know the strategy of development which is applied in developing the natural tourism objects. The methode in this research is descriptive qualitative and quantitative. It is descriptive because this research aims to describe the phenomena of tourism objects systematically, factually, and accurately regarding the facts and the relations among phenomena which are studied. Based on the scoring analysis of each natural tourism object, Sungai Tamborasi has a category level of high potential with most of variables of these tourism objects are the supporting factors, meanwhile, Tanjung Malaaha is a tourism object that has the lowest score with the category of moderate potential that means that the supporting factors and the obstructive factors are equal in their characteristic. The results of the research showed that the supporting factors of the natural tourism objects of Kolaka are: the beautiful and original natural panorama, the society's openness on the tourists, the good security, the completeness of the means of the main transportation, and the various uniqueness. The obstructive factors of the natural tourism objects of Kolaka are: the obstruction in the development, the limitation in the infrastructure of the natural tourism objects, the lack of public transportation for reaching each object, the lack of professional human resources to manage the tourism objects, the inadequate promotion of the natural tourism objects. From the results of the SWOT analysis, the priority direction of t he development of these natural tourism objects is maintaining the variety and the tourism enchantment by increasing the intensity of direct attention from the authorities, increasing the infrastructure which supports the tourism, making a special website to promote the tourism objects, and finally, planning the controlled and professional development by the use of the more and more cooperative attitude of the government side on other agencies. Keywords: Natural Tourism Object, Potential, Development.